Analysis of the Technology Acceptance Model (TAM) on the Use of Software for Students in the Building Engineering Education Program - Arisman Telaumbanua; Aprianus Telaumbanua; Rena Ria Zalukhu (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to analyze the Technology Acceptance Model (TAM) regarding the usage of software among students of the Building Engineering Education Program. The research method to be used is associative research method. The population in this study consists of students of the Building Engineering Education Program at the Faculty of Teacher Training and Education, Universitas Nias, who are active in the Odd Semester of the Academic Year 2023/2024. This population comprises students in the 3rd, 5th, and 7th semesters, with a total of 61. The data analysis method used is Structural Equation Modeling (SEM). The research results conclude that perceived ease of use significantly influences behavioral intention to use regarding the usage of software for students of the Building Engineering Education Program, perceived usefulness significantly influences behavioral intention to use regarding the usage of software for students of the Building Engineering Education Program, and behavioral intention to use significantly influences perceived usage regarding the usage of software for students of the Building Engineering Education Program.